Modeling the Transport of Nuclear Proteins Along Single Skeletal Muscle Cells - Teixeira, Ana (Karolinska Institutet, 2020)
The purpose of this study was to define the factors that control the distribution of nuclear proteins in multinucleated skeletal muscle cells (myotubes). Nuclear-targeted red fluorescent proteins of different molecular weights were used as a model protein. Changes in their distributions were quantified as a result of perturbations causing myotube hypertrophy, atrophy, and diminished nuclear import rates. A computational model was developed to simulate nuclear protein distribution using a combination of empirical values and data from the literature. Finally, the results from the model system were then validated using muscle-related transcription factors ARNT and Six1.

These data were generated to study the distribution of nuclear proteins within multi-nucleated skeletal muscle cells. Myotubes were produced by differentiating primary mouse myoblasts that were sparsely transfected to express a nuclear protein from a single nucleus. From the microscopy images, we measured the protein intensity in all nuclei along with the distance of each nucleus from the brightest one, which was assumed to be the transfected nucleus. We used these distribution profiles to study the relationship between protein size and its transport behavior. We also studied the effect of treatments that induce cell hypertrophy (capsaicin), atrophy (dexamethasone), and diminished nuclear import (importazole) on the transport of the nuclear proteins. We also developed a mathematical model to simulate how changes in cell and protein properties affect protein transport. These data form the basis of the figures in the associated manuscript, and the detailed methods pertaining to their collection can be found there. The data have been organized according to their corresponding figure.

Figure 1 - Nuclear protein transport dynamics
Using time-lapse microscopy, we captured the transport of the DsRed red fluorescent protein (RFP) at 6, 12, 18, and 24 hours after induction of expression (Fig 1 - 1-4). We also included a Hoechst nuclear counterstain at the final timepoint (24 hours, Fig 1 - 5)

Figure 2 - Molecular weight affects nuclear protein transport
These data show the distribution profiles of mCherry, tdTomato, and DsRed RFP variants in myotubes after three days of differentiation and one day of expression. The images are fluorescence microscopy images with one channel containing the RFP signal and the other a nuclear counterstain. The filenames indicate which RFP is used.

Figure 3 - Perturbing nuclear import affects nuclear protein transport
In these images, cells were treated as previously with the addition of 5 μM importazole added during the final 24 hours to reduce the rate of protein import into nuclei. The filenames indicate which RFP is used.

Figure 4 - Cell morphology affects nuclear protein transport
In these images, cells were treated as previously with the addition of either 10 μM capsaicin or 10 μM dexamethasone during the final 24 hours to induce hypertrophy or atrophy, respectively. The drugs modulated cell width, which in turn affected the distribution profiles of the nuclear proteins. The filenames indicate which drug and RFP are used.

Figure 5 - Mathematical model to simulate nuclear protein transport
Here, a computational MATLAB model was developed to simulate the effects of various cell and protein properties on nuclear protein distribution.

Figure 6 - Transport of muscle transcription factors
To validate the results derived with RFP nuclear proteins, we repeated the experiments using ARNT-CFP and Six1-myc transcription factors expressed in muscle. ARNT-CFP has a similar size to DsRed, while Six1-myc is similar to mCherry. The images contain two channels (either ARNT-CFP signal and DRAQ5 nuclear coutnerstain or Six1-myc and Hoechst nuclear counterstain). The filenames indicate which transcription factor is used.

Syftet med denna studie var att definiera de faktorer som påverkar fördelningen av cellkärneproteiner i flerkärniga skelettmuskelceller (myotuber). Kärnuppsökande röda fluorescerande proteiner av olika molekylvikt användes som modell. Förändringar i deras fördelning beräknades som en följd av störningar som orsakade hypertrofi, atrofi och reducerad intransport av kärnor hos myotuberna. I kombination med mätvärden från litteraturen utvecklades en beräkningsmodell som kan simulera fördelningen av kärnprotein. Slutligen bekräftades resultaten från modellsystemet med hjälp av de muskelförekommande transkriptionsfaktorerna ARNT och Six1.

Denna studie genomfördes för att studera fördelningen av kärnproteiner i flerkärniga skelettmuskelceller. Myotuber framställdes genom att differentiera primära myoblaster från mus som sparsamt transfekterades för att uttrycka kärnprotein från en enda kärna. Från mikroskopibilderna mätte vi proteinintensiteten hos alla kärnor, samt distansen mellan varje kärna och den starkast lysande kärnan, vilken antogs vara den som tranfekterats. Vi använde dessa fördelningsprofiler för att studera förhållandet mellan ett proteins storlek och dess transportsätt. Vidare undersökte effekten av behandlingar som framkallar cellhypertrofi (kapsaicin), -atrofi (dexametason), och reducerad intransport till kärnor (importazole) på kärnproteintransport. Dessutom utvecklade vi en matematisk modell som simulerar hur förändringar i cell- och proteinegenskaper påverkar proteintransport. Dessa data utgör basen för figurerna i det bifogade manuskriptet, som även innehåller de experimentella metoderna i detalj. Datan har organiserats enligt motsvarande figur.

Figur 1 - Transportdynamik för proteinimport till cellkärnan
Vi tog mikroskopbilder 6, 12, 18 och 24 timmar efter att uttrycket av DsRed inducerats, för att kartlägga transporten av de röda fluorescerande proteinerna (RFP, Fig. 1-4). Vi inkluderade även en Hoechst motfärgning vid den sista intervallen (24 h, Fig. 1-5).

Figur 2 - Molekylärvikten påverkar kärnproteintransport
Här visas fördelningsprofilerna av RFP-varianterna mCherry, tdTomato och DsRed i myotuber efter tre dagars celldifferentiering och en dag av genuttryck. Bilderna kommer från fluorescensmikroskop och innehåller två kanaler; en med RFP-signalen, och den andra med en motfärgning. Filnamnen indikerar vilket RFP som använts.

Figur 3 - Störning av intransport till cellkärnor påverkar kärnproteintransport
Cellerna i dessa bilder behandlades under de sista 24 timmarna med 5uM importazole för att minska intransporten av proteiner till cellkärnorna. Filnamnen indikerar vilket RFP som använts.

Figur 4 - Cellens morfologi påverkar kärnproteintransport
Cellerna i dessa bilder behandlades under de sista 24 timmarna med antigen 10 uM kapsaicin eller 10 uM dexametason för att framkalla hypertrofi respektive atrofi. Dessa behandlingar förändrar cellens bredd, vilket påverkar fördelningen av kärnproteiner. Filnamnen indikerar vilken behandling och vilket RFP som använts.

Figur 5 - Beräkningsmodell som simulerar kärnproteintransport.
En modell utvecklades i MATLAB för att simulera hur olika egenskaper hos celler och proteiner påverkar fördelningen av kärnproteiner.

Figur 6 - Transport av muskelrelaterade transriptionsfaktorer
För att styrka resultaten som gavs av RFP-modellen repeterades experimenten med de muskelförekommande transkriptionsfaktorerna ARNT-CFP och Six1-myc. Storleksmässigt liknar ARNT-CFP DsRed, och Six1-myc liknar mCherry. Bilderna innehåller två kanaler; ARNT-CFP med motfärgningen DRAQ5, och Six1-myc med motfärgningen Hoechst. Filnamnen indikerar vilken transkriptionsfaktor som använts.
Modell för transport av kärnproteiner längs enskilda skelettmuskelceller
Keywords: skeletal muscle; skelettmuskulatur; myonuclear domain; myonukleär domän; nuclear transport; nukleär transport; mathematical model; matematisk modell; Medical and Health Sciences; Medicin och hälsovetenskap